MODERNIZING TRADITIONAL MEDICINES IN JAVA: REGULATIONS, PRODUCTION AND DISTRIBUTION NETWORKS - Nawiyanto, Nawiyanto (History Department, Semarang State University and Historian Society of Indonesia, 2016)
Traditional medicine (jamu) in Indonesia is continuously transforming due to a number of factors including the growing presence of the biomedical system promoted by the government and drug manufacturers, the requirement of more standardized and scientifically-proven medicinal products, and the declining popularity of herbal medicine among the young generation. Traditional medicines producers need to adjust continuously to the changing environment. This article seeks to examine these transformations by taking Java as its focus of attention. There are two major reasons for this choice. First, the island of Java is home for many traditional medicines producers, both small-scale, home-based industries and large-scale, company-based industries. Second, the largest proportion of the users of traditional medicines and distribution networks are also found in the island. The major questions the article seeks to address are: (1) what regulations have been set in place by the state authorities with regard to the production and distribution of traditional medicines in Java? How do the producers and the related partied respond the regulations?; (2) what efforts have been made by the producers of traditional medicines to accept modernization challenges and to improve the performance of their products; (3) how traditional medicines circulate and what are their distribution networks?Â Obat tradisional (jamu) di Indonesia terus berubah karena sejumlah faktor termasuk semakin tumbuhnya kehadirani sistem biomedis dipromosikan oleh pemerintah dan produsen obat, kebutuhan akan produk obat yang lebih standar dan terbukti secara ilmiah, dan menurunnya popularitas jamu di kalangan generasi muda. Produsen obat tradisional produsen perlu menyesuaikan terus menerus terhadap lingkungan yang berubah. Artikel ini ditujukan untuk mengkaji transformasi ini dengan mengambil Jawa sebagai fokus perhatian. Ada dua alasan utama untuk pilihan ini. Pertama, pulau Jawa adalah tempat bagi banyak produsen obat-obatan tradisional, baik skala kecil, industri rumahan dan skala besar, industri berbasis perusahaan. Kedua, proporsi terbesar dari para pengguna obat-obatan tradisional dan jaringan distribusi juga ditemukan di pulau ini. Pertanyaan-pertanyaan utama yang hendak dijawab dalam artikel ini adalah: (1) peraturan apakah yang telah ditetapkan oleh otoritas negara yang berkaitan dengan produksi dan distribusi obat-obatan tradisional di Jawa? Bagaimana respons produsen dan pihak terkait terhadap peraturan-peraturan yang berlaku?; (2) upaya apakah yang telah dilakukan oleh produsen obat tradisional untuk menjawab tantangan modernisasi dan untuk meningkatkan kinerja produk mereka; (3) bagaimana obat tradisional beredar dan apa jaringan distribusinya?Â